Ժամանակակից կյանքի դրաման Հովհաննես Մելքոնյանի ստեղծագործության մեջ - Օֆելյա Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
О. Мелконян по художественному восприятию уникальный автор. Реальный факт жизни, в какой временной зоне он бы ни был, О. Мелконян обрабатывает с точки зрения истинного автора, рассматривая его со всех сторон. Hovhannes Melkonyan is an author of unique artistic mentality and temperament. He studies and enhances the actual facts of life of any period from different angles with the apprehensive approach of a real author.
Keywords: Philology; Linguistics; Language and Literature